A Review of Generative AI in Higher Education - Brent Yan (Brock Education: a Journal of Educational Research and Practice)
Generative AI in higher education: the ChatGPT effect, by Cecilia Ka Yuk Chan and Tom Colloton, New York, Routledge, 2024, 278 pp., £32.99 (paperback) ISBN 9781032599045